The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1212/wnl.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors, large-artery atheroma, and brain white matter hyperintensities

Abstract: Objective:To determine the magnitude of potentially causal relationships among vascular risk factors (VRFs), large-artery atheromatous disease (LAD), and cerebral white matter hyperintensities (WMH) in 2 prospective cohorts.Methods:We assessed VRFs (history and measured variables), LAD (in carotid, coronary, and leg arteries), and WMH (on structural MRI, visual scores and volume) in: (a) community-dwelling older subjects of the Lothian Birth Cohort 1936, and (b) patients with recent nondisabling stroke. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
187
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(206 citation statements)
references
References 38 publications
17
187
2
Order By: Relevance
“…However, it has since been shown that all vascular risk factors combined account for o2% of the variance in white matter hyperintensities. 2 Furthermore, despite major advances in blood pressure control, the incidence of SVD remains high, and this has failed to prevent the progression of white matter hyperintensities or lacunar stroke, 35 suggesting that other risk factors may be crucial to disease progression. Recent evidence from animal models also suggest that hypertension is not the key driver of white matter changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has since been shown that all vascular risk factors combined account for o2% of the variance in white matter hyperintensities. 2 Furthermore, despite major advances in blood pressure control, the incidence of SVD remains high, and this has failed to prevent the progression of white matter hyperintensities or lacunar stroke, 35 suggesting that other risk factors may be crucial to disease progression. Recent evidence from animal models also suggest that hypertension is not the key driver of white matter changes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hypertension is proposed to be a common risk factor (although it explains only a small proportion of imaging-determined SVD) and cerebral amyloid angiopathy is commonly present on pathologic examination. 2,3 Clinically, SVD is associated with early impairment of attention and executive function with slowing of information processing and motor deficits. 1 These clinical manifestations result primarily from the occurrence of lesions in the cerebral white matter, multiple lacunes within subcortical structures, atrophy, and, in some cases, microbleeds in deep gray matter, white matter, or at the corticosubcortical junction, identified by neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it might be plausible that hypertensioninduced vascular changes have a relatively minor contribution to development of human cerebral white matter hyperintensities as demonstrated in a recent cohort study of 881 community-dwelling old subjects and 257 patients with recent nondisabling stroke. 21 The current new model (SHR-2VGO) appears to include at least some important elements of the entire process of Binswanger disease, a pathological condition of SIVD, 22 leading from the initial process of hypertension to subsequent brain damage, whereas the existing models, such as WKY-2VO or WKY-2VGO, simulate only the downstream part of the pathophysiological cascade of small vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinically lacunar stroke and SVD are associated with some vascular risk factors such as hypertension, diabetes and smoking but have only weak associations with others such as large artery atheroma and atrial fibrillation. 5,6 While some SVD imaging features and large artery stroke can occur in the same individuals, in general, recurrent stroke tends to be of the same type as the initial stroke. 7 Additionally, SVD features associate more strongly with lacunar than cortical stroke.…”
Section: Introductionmentioning
confidence: 99%